The Role of Halal Label to Increase the Effect of Attitude Toward Halal Product on Brand Image and Purchase Intention - Nur Hidayati; Hadi Sunaryo (IJEBD (International Journal of Entrepreneurship and Business Development), 2021)
Purpose: The purpose of this study was to examine the role of halal labels in affecting attitude toward halal products on brand image and purchase intention among Muslim consumers in Malang. Design/methodology/approach: Quantitative methods were employed in this study to reveal the important role of attitude toward halal directly on brand image and purchase intention or indirectly through halal label. In addition to analyzing the direct and indirect effects, this study also confirms how the relationship and significance between each construct and its indicators. Findings: The results of the research findings indicate that each effect on the relationship between variables was found to be significant. The most important determinant of halal labeling is halal product attitude. Meanwhile, the halal label is the most important factor in encouraging brand image and purchase intention. Research limitations/implications: Discussion of Islamic branding especially in the halal label can be considered as a separate theoretical study. It is considered that the epistemological basis of Islamic marketing theory, models, and approaches is rather limited in terms of its development. Practical implications: This research provides practical implications about the importance of halal product management by product marketers in the Malang area Originality/value: There is an increasing need for clarifying the need to establish a theoretical framework for Islamic Branding with Halal Labels when they intersect as in terms of Islamic concepts, theories, models and approaches.